Adsorption of phenanthrene onto magnetic multi-walled carbon nanotubes (MMWCNTs) influenced by various fractions of humic acid from a single soil. (August 2021) - Cao, Huimin; Zhang, Peng; Jia, Weili; Wang, Cuiping; Xing, Baoshan
Abstract: In the present study, two magnetic multi-walled carbon nanotubes (MMWCNTs) with different ratios of Fe 2+ /Fe 3+ were prepared, and the effects of different fractions of dissolved humic acid (DHA) on the adsorption of phenanthrene by multi-walled carbon nanotubes (MWCNTs) and MMWCNTs from the aqueous solution were investigated. The adsorption kinetics of DHA1 and DHA4 were best fitted with pseudo-second order model. The adsorption of DHAs on MMWCNTs was weaker than that on MWCNTs, and DHA1 was easier to adsorb to MWCNTs and MMWCNTs than DHA4 . The phenanthrene adsorption capacities by 1:2:1MMWCNTs and 4:2:1MMWCNTs with higher polar groups and magnetic gradient were less than that of MWCNTs. The pH value had no obvious effect on the adsorption of phenanthrene to MWCNTs loaded with different iron. Additionally, the DHAs could form soluble complexes of DHAs–Fe (II) in solution to reduce the phenanthrene adsorption on MMWCNTs, DHA1 inhibit more obviously phenanthrene adsorbed onto MWCNTs and MMWCNTs than DHA4 . As for MMWCNTs, the main mechanisms of phenanthrene adsorbed onto it included new adsorption sites formed by π−π interaction and magnetic gradient. In this study, MMWCNTs after adsorbed DHAs had a weaker inhibitory effect on phenanthrene adsorption than MWCNTs, implying that when phenanthrene is adsorbed by DHAs-coated MMWCNTs, the bioavailability and mobility of phenanthrene will be reduced, and it is easy to be removed by the magnet for further processing. Highlights: The adsorption of DHAs on MMWCNTs was weaker than that on MWCNTs. The phenanthrene adsorption capacities by MMWCNTs was less than MWCNTs. The pH value had no obvious effect on the adsorption of phenanthrene to MMWCNTs. DHAs inhibit the phenanthrene adsorbed on to MWCNTs and MMWCNTs. DHA1 had a stronger inhibitory effect than DHA4 .